2006
DOI: 10.1136/bmj.38726.603310.55
|View full text |Cite
|
Sign up to set email alerts
|

Sham device v inert pill: randomised controlled trial of two placebo treatments

Abstract: Objective To investigate whether a sham device (a validated sham acupuncture needle) has a greater placebo effect than an inert pill in patients with persistent arm pain. Design A single blind randomised controlled trial created from the two week placebo run-in periods for two nested trials that compared acupuncture and amitriptyline with their respective placebo controls. Comparison of participants who remained on placebo continued beyond the run-in period to the end of the study. Setting Academic medical cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
286
0
12

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 466 publications
(307 citation statements)
references
References 22 publications
7
286
0
12
Order By: Relevance
“…Intensity: More intensive medical procedures produce greater placebo effects (Kaptchuk et al, 2006).…”
Section: Demand Characteristicsmentioning
confidence: 99%
“…Intensity: More intensive medical procedures produce greater placebo effects (Kaptchuk et al, 2006).…”
Section: Demand Characteristicsmentioning
confidence: 99%
“…Acupuncture is well known for its powerful nonspecific/placebo effect. 25 One possible interpretation could be that the analgesic effect of acupuncture did not reach a significantly different level from that of the control group, but that women receiving acupuncture may have felt that they are being given something, thus did not require more analgesic methods.…”
Section: Subtotal (95% Ci)mentioning
confidence: 99%
“…Invasive treatment techniques are almost always perceived by patients as profoundly meaningful, and such a strong "meaning response" [25] could contribute to symptom reduction [26,27]. Indeed, Kaptchuk et al have directly compared placebo pills and sham acupuncture in a randomised trial and found the latter to be more effective [27]. It may also be that our sham technique has physiologic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Along with other groups [22][23][24], we have observed that both acupuncture forms are invasive treatments. Invasive treatment techniques are almost always perceived by patients as profoundly meaningful, and such a strong "meaning response" [25] could contribute to symptom reduction [26,27]. Indeed, Kaptchuk et al have directly compared placebo pills and sham acupuncture in a randomised trial and found the latter to be more effective [27].…”
Section: Discussionmentioning
confidence: 99%